PALEONTOLOGI FORMASI NYALINDUNG - -, Syarifin (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Nyalindung area is known for its collection of abundant mollusca fauna. That fossils are contained in the sandstone and silt. Nyalindung area became a location type for Nyalindung Formation. Nyalindung Formation spread from the north district Nyalindung, there is along Cimandiri drainage area, to Bantarkalong Village and Cimerang high plains. This formation is spread to Bojonglopang shoutheastern, there is along the road of Nyalindung-Bojonglopang.Determination of age based on the collection of molluscas. Found 18% of Recent species that show Miocene age, based on clues fossil prompts (Siposiprarea caputviverae and Vicaria veurnelli Calossa) that indicate of Middle Miocene age. Based on forams L. (tribiolepidina) ruteeni and L. (tribiolepidina) kalahabensis showed Tf-3 age. Deposition environment of Nyalindung Formation based on lithology, paleontology and sedimentary structures. As a whole of deposition occurs in the open sea in the vicinity of Cileungsir river to estuaries up around the marshy area of western and eastern section investigation.